Efisiensi Biosorpsi Logam Cr (VI) Menggunakan Spent Mushroom Substrate (SMS) Coprinus Comatus Yang Diaktivasi Oleh NaOH - Hany Susanti Pangaribuan; Elvi Yenie; Atria Martina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Metal Cr (VI) is a heavy metal contained in electroplating wastewater which is very stable and dangerous for the environment and human health. This study aims to determine the ability of SMS C. comatus in removing metal Cr (VI) in electroplating wasteswater with mass 3 grams, biosorption contact time 30 minutes with activation treatment using NaOH (0,3N) and activation time 15,30 and 45 minutes. The allowance made by SMS C. comatus in reducing Cr (VI) in electroplating wastewater with initial concentration of Cr (VI) 47.23 mg/L with the highest efficiency value of 39.02 % in activation time 45 minutes. Keywords: biosorption, Spent Mushroom Substrate (SMS), electroplating wastewater